Stock price reaction and value relevance of recognition versus disclosure: the case of stock-based compensation - Espahbodi, Hassan; Espahbodi, Pouran; Rezaee, Zabihollah; Tehranian, Hassan (Journal of Accounting and Economics, 2002)
This study examines the equity price reaction to the pronouncements related to accounting for stock-based compensation and assesses the value relevance of recognition versus disclosure in financial reporting. We document that firms exhibit significant abnormal returns around the issuance of the Exposure Drafts proposing to require recognition of stock-based compensation costs, and also around the event reversing that decision to require disclosure only (while encouraging recognition). We also document that the abnormal returns are most pronounced for high-tech, high-growth, and start-up firms. Our results are consistent with the contracting theory, and show that disclosure is not a substitute for recognition.